[Cu3(C6Se6)]n: The First Highly Conductive 2D π–d Conjugated Coordination Polymer Based on Benzenehexaselenolate - Yutao Cui; Jie Yan; Zhijun Chen; Jiajia Zhang; Ye Zou; Yimeng Sun; Wei Xu; Daoben Zhu (Advanced Science, 2019)
Abstract Nanocrystals of a 2D π–d conjugated copper bis(diselenolene) coordination polymer (Cu‐BHS, BHS = benzenehexaselenolate) are synthesized via a simple homogeneous reaction between cupric ions and benzenehexaselenol (H6BHS). Its 2D extended hexagonal lattice is confirmed by powder X‐ray diffraction, and further characterized by scanning electron microscopy, transmission electron microscopy, and X‐ray photoelectron spectroscopy. The electrical conductivity measured on compressed powder sample reaches 110 S cm−1 at 300 K, which is among the highest value ever reported for coordination polymers. Furthermore, the intrinsic metallic characteristics of Cu‐BHS are confirmed by ultraviolet photoelectron spectroscopy and band structure calculation.